Design and simulation of bionic glove for rehabilitation of the paralytics - B, Aparna; B, Anithakrithi; P, Naveena; Kumar M, Yaswanth; M, Avinash; Sivanandam, S (International Journal of Engineering and Technology, 2018)
Repetitive therapy can improve dexterity and hand movement among the paralyzed and stroke affected patients. The assistance of simple robotic technology may enhance the recovery rate of such patients. The study aims at developing a low cost bionic glove rehabilitation device which aids in providing effective finger exercises for physiotherapy by the use of a potentiometer. The prototype is designed in the form of a wearable glove for easy use. It includes an ATMEGA-328 microcontroller that is programmed using Arduino software for controlling the device. The motion of the fingers during therapy is achieved using a metal gear servo motor while the linear potentiometer controls the angle. This device can be used in rehabilitation to provide repetitive therapy for fingers at home with limited supervision by the physiotherapist for the paralytics. The performance of the device is simulated and evaluated using the Proteus Intelligent Schematic Input System (ISIS) software. The results obtained from the simulation can be used to improve the features of the device for effective practical implementation.